2015
DOI: 10.7567/jjap.54.065702
|View full text |Cite
|
Sign up to set email alerts
|

Unusual energy separation of subbands in Si(111) p-channels induced by In adsorption

Abstract: The probe method gives a general idea to obtain a reconstruction formula of unknown objects embedded in a known background medium from a mathematical counterpart (the Dirichlet-to-Neumann map) of the measured data of some physical quantity on the boundary of the medium. It is based on the sequence of special solutions of the governing equation for the background medium related to a singular solution of the equation. In this paper the blowup property of the sequence is clarified. Moreover a new formulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Subband energy levels at the gamma point are compared with the theoretical values obtained by triangular potential approximation(TPA). Though the measured energy levels were in good agreement with the theoretical values in most cases, significant deviation was observed in some cases [2,4,5]. In the case of Pb/Si(001) [5], the origin of the deviation was speculated to be the reduction of dopant concentration caused by dopant outdiffusion during flash annealing process [6], which is a conventional method to make a clean silicon surface.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Subband energy levels at the gamma point are compared with the theoretical values obtained by triangular potential approximation(TPA). Though the measured energy levels were in good agreement with the theoretical values in most cases, significant deviation was observed in some cases [2,4,5]. In the case of Pb/Si(001) [5], the origin of the deviation was speculated to be the reduction of dopant concentration caused by dopant outdiffusion during flash annealing process [6], which is a conventional method to make a clean silicon surface.…”
Section: Introductionsupporting
confidence: 54%
“…Hole subbands, quantized electronic structure confined in silicon inversion layer (IL), has been recently observed by ARPES in the system of In/Si(111) [1,2], Pb/Si(111) [3], PbGa/Si(111) [4] and Pb/Si(001) [5]. The subband dispersion structures were clearly detected in these works.…”
Section: Introductionmentioning
confidence: 70%
“…1(a), 1(b)] has been reported using ultra-violet photoelectron spectroscopy. [8][9][10][11][12][13][14] Through the studies, some of the observed subbands quantum levels were found to be inconsistent with the result of the triangular potential approximation (TPA) calculation. In the TPA, the band edge profile V(z) in the space charge layer is approximated to a linear line so that the subband energy levels are obtained analytically.…”
Section: Introductionmentioning
confidence: 90%
“…In most cases, 8,11,14) the observed energy separations agree with the results from the TPA calculations. However, in some cases, 9,10,13) especially when the dopant concentration of the substrate is higher than 1 × 10 −19 cm −3 , the observed ground subband E 0 was significantly closer to the confinement potential bottom V 0 , which is the valence band edge at the surface V(z = 0). In the case of Ref.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation